Development of learning media for understanding procedure text based on powtoon application for class VII students of SMP Srijaya Negara - Emelia Sucini; Nurhayati Nurhayati; Izzah Izzah (Journal of Learning Improvement and Lesson Study, 2021)
The reasons for using learning media are important in learning, namely improving the quality of learning, the demands of a new paradigm, market needs, and the vision of global education. This study aims to describe the results of the analysis of the needs of seventh grade students and teachers of SMP Srijaya Negara Palembang for the instructional media for understanding the powtoon application-based procedural text, describe the design of understanding the powtoon application-based procedural text, and describe the results of the validation. expert on powtoon application-based learning media. This study uses a research method that refers to the modified Alessi & Trollip research and development model, namely (1) the planning stage, (2) the design stage, and (3) the development stage. The instructional media for understanding the text of this procedure was developed based on the results of the analysis of the needs of students and teachers. The results show that the overall learning media for understanding procedure text based on the powtoon applicationis declared valid.